2018
DOI: 10.1016/j.ejmech.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Novel indole-thiazolidinone conjugates: Design, synthesis and whole-cell phenotypic evaluation as a novel class of antimicrobial agents

Abstract: In connection with our research program on the development of novel anti-tubercular candidates, herein we report the design and synthesis of two different sets of indole-thiazolidinone conjugates (8a,b; 11a-d) and (14a-k; 15a-h). The target compounds were evaluated for their in vitro antibacterial and antifungal activities against selected human pathogens viz. Staphylococcus aureus (Gram positiveve), Pseudomonas aeruginosa, Escherichia coli (Gram negative), Mycobacterium tuberculosis (Acid-fast bacteria), Aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…The methoxy, ethoxy, and alkyl groups were found to be favorable for the activity. Compounds (18) (MIC = 0.39 μg/mL) were more and equally potent compared to standard drug isoniazid, (MIC = 0.78 μg/mL) 78 .…”
Section: Anti-tubercular Activity: Tuberculosis Is Global and Deadly mentioning
confidence: 96%
See 2 more Smart Citations
“…The methoxy, ethoxy, and alkyl groups were found to be favorable for the activity. Compounds (18) (MIC = 0.39 μg/mL) were more and equally potent compared to standard drug isoniazid, (MIC = 0.78 μg/mL) 78 .…”
Section: Anti-tubercular Activity: Tuberculosis Is Global and Deadly mentioning
confidence: 96%
“…SAR (structural activity relationship) study concluded that chloro and methyl substitution are favorable for the activity. Compound (2) (MIC < 0.98 μg/mL) was established to be nearly all active with equal potency both as antifungal and as antimicrobial relative to ciprofloxacin (MIC < 3.90 μg/mL) and amphotericin B (MIC < 1.95 μg/mL), respectively 55 . Recently, synthesized and evaluated various indole derivatives containing heterocyclic nucleus were explored as antimicrobial agents.…”
Section: Evaluation Of Indole Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…sulfonamides and their bioisosteres, carboxylates and their derivatives, phenols, and so on). Thiazolidinones were recently assayed as potent antifungal agents [39,40], and some of them were tested as carbonic anhydrase inhibitors in order to discover and develop innovative mechanisms of inhibition [37,41]. From the data reported in Table 2, it is possible to extrapolate a very remarkable selectivity profile of our thiazolidinones against this fungal β-CA over the two ubiquitous human isoforms (hCA I and II) being the selectivity index (SI) for compound 4h > 1000 (expressed as the ratio between K I CA I or II and K I CgNce103 values) and >100 for most of the other compounds.…”
Section: Enzyme Inhibition Studies Of Cgnce103 Compared To Hca I and Iimentioning
confidence: 99%
“…Isatins have emerged as antimicrobial agents due to their broad spectrum of in vitro and in vivo antimicrobial activities [19][20][21][22][23][24][25][26][27]. In addition, thiazolidinone also reported to possess various biological activities particularly antimicrobial activity [28][29][30][31][32]. Due to the importance, we planned to synthesize compounds with isatin functionality coupled with thiazolidinone as possible antitubercular and antimicrobial agents which could furnish better therapeutic results.…”
Section: Introductionmentioning
confidence: 99%